3D printed continuous wire polymer composites strain sensors for structural health monitoring. (10th September 2019) - Saleh, Menna A; Kempers, Roger; Melenka, Garrett W
Abstract: This study presents the electromechanical properties of three-dimensional (3D) printed unidirectional continuous wire polymer composite (CWPC) to study the correlation of the elastic mechanical deformation and the electrical resistance under uniaxial loading conditions. Two kinds of wires were used for this study: copper (Cu) and nichrome (NiCr). 3D printing was utilized due to its flexibility in design and structure for different applications. From mechanical testing, the NiCr CWPCs demonstrated an increase of 13.5% and 54% in ultimate tensile strength and Young's modulus, respectively, compared to pure 3D printed Poly(lactic acid) while the Cu CWPC did not exhibit significant improvement in the mechanical properties. A direct linear relationship was observed between the applied tensile strain and the measured electrical resistance for both Cu and NiCr CWPCs indicating the ability of these 3D printed structures to be used as a sensor to measure stress/strain in the real time. In addition, the sensitivity of both composites in terms of gauge factor, representing the relative change in the electrical resistance with the tensile strain of the material, were found to be 1.17 ± 0.06 and 1.13 ± 0.07 for Cu and NiCr CWPCs, respectively. This sensitivity was compared with a simple analytical model and showed a good agreement with the experimental results. Finally, the reliability of these CWPCs was evaluated by conducting a cyclic loading test within their elastic ranges. The results of this work will enable the manufacture of integrated sensors within 3D printed components with improved mechanical properties and increased functionality.